If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -2) + 3(3x + -1) = 3x + 70 Reorder the terms: 4(-2 + 3x) + 3(3x + -1) = 3x + 70 (-2 * 4 + 3x * 4) + 3(3x + -1) = 3x + 70 (-8 + 12x) + 3(3x + -1) = 3x + 70 Reorder the terms: -8 + 12x + 3(-1 + 3x) = 3x + 70 -8 + 12x + (-1 * 3 + 3x * 3) = 3x + 70 -8 + 12x + (-3 + 9x) = 3x + 70 Reorder the terms: -8 + -3 + 12x + 9x = 3x + 70 Combine like terms: -8 + -3 = -11 -11 + 12x + 9x = 3x + 70 Combine like terms: 12x + 9x = 21x -11 + 21x = 3x + 70 Reorder the terms: -11 + 21x = 70 + 3x Solving -11 + 21x = 70 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -11 + 21x + -3x = 70 + 3x + -3x Combine like terms: 21x + -3x = 18x -11 + 18x = 70 + 3x + -3x Combine like terms: 3x + -3x = 0 -11 + 18x = 70 + 0 -11 + 18x = 70 Add '11' to each side of the equation. -11 + 11 + 18x = 70 + 11 Combine like terms: -11 + 11 = 0 0 + 18x = 70 + 11 18x = 70 + 11 Combine like terms: 70 + 11 = 81 18x = 81 Divide each side by '18'. x = 4.5 Simplifying x = 4.5
| 2(x)+2(1.6x)=234 | | x-4=-9 | | 10-3(2x+5)=7 | | 3(2x-5)-(2x-4)=6-(4x+5) | | v+34=90 | | 8-4(m+5)=3(m-9) | | -4(p-5)=0 | | 141-6x=39x+21 | | 5(2x-10)-4=5(x-3)+1 | | 3x-6y=6 | | 11.25x=1000 | | 109-4x=14x+17 | | 1.6x=286 | | 4y+8=3x | | 11-10x=175-38x | | 6-7x=-36 | | 11x=21-2x^2 | | m(3m+2)=0 | | 0.3(5n+12)+0.3n=-1 | | 5p+7-2(p-5)=2 | | 8x+11=55 | | x^4+x^3-2x^2=0 | | X^2+10x-24= | | -44.2x^2-6=-20.6x^2-23.8 | | X^2-xy-10= | | 2x+20=4y | | 113-5x=4x+14 | | x^3+2x^2-40x-25=0 | | 2x^2-31=1 | | 0.83e+18-0.16e=6 | | 3x+6=2x+20 | | 9-7x=-40 |